Sistem Penilaian Prestasi Kerja pada PT. Bank Negara Indonesia (Persero) Tbk Kantor Cabang Syari'ah Pekanbaru, Riau - Zulkifli Rusby; Muhammad Arif; Ahmad Hidayatullah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
Performance appraisal is a work achieved by a person in carrying out the tasks assigned to him based on skill, experience and sincerity as well as time. In this study the authors wanted to know the job performance evaluation system at PT. Bank Negara Indonesia (PERSERO) Tbk Syari'ah Pekanbaru Branch Office by focusing on 5 (five) research variables, and in this study can be seen as follows: (1) Achievement of Achievement, based on the results of processed and data analysis of respondents' answers obtained 71, 61%. (2) Building Trust, based on the results of the processed and data analysis of respondents' answers obtained 70.31%. (3) Focus on Customers, based on the results of processed and data analysis of respondents' answers obtained 69.27%. (4) Orientation on Quality, based on the results of the processed and data analysis of respondents' answers obtained 75.78%. (5) Cooperation, based on the results of the processed and data analysis of respondents' answers obtained 68.35%. And in this study it can be seen that the performance appraisal system at PT. Bank Negara Indonesia (PERSERO) Tbk Syari'ah Pekanbaru Branch Office has almost reached the effective level or can be said to be